"Pyrimethamine and Proguanil Resistance-Conferring Key Mutations in Dihydrofolate Reductase Gene of Plasmodium falciparum Isolates from Iran" - AA Eskandarian; H Keshavarz; F Mahboudi (Tehran University of Medical Sciences, 2003)
Using mutation specific PCR assay and analysis of position 108 amino acid in dihydrofolate reductase-thymidilate synthase gene in 70 Plasmodium falciparum isolates of malarial patients from southern areas of Iran, showed 4 different situations: iwild type (108-Ser) ii-mutant type (108-Thr) iii-mutant type (108-Asn) and iv-mixed wild and mutant type (108-Ser+Thr) with frequency of 58(82.8%), 2(2.9%), 8(11.4%) and 2(2.9%) respectively. Many studies have demonstrated that mutations in position 108 have key role for emerging resistance to anti-folate drugs in falciparum malaria so, the resistance to pyrimethamine and proguanil, presents in Plasmodium falciparum isolates from malarious endemic regions of Iran.